BEYOND THE BASICS: UNVEILING HIDDEN GEMS IN EMPLOYEE SATISFACTION - Erma Shahida Kaap; Natalia Hakimi; Noorhidayah Salehhudin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
In the 21st century, employees possess a fundamentally distinct set of expectations compared to prior generations of workers. Employee satisfaction refers to the positive emotional state that employees experience towards their work, colleagues, and the overall work environment. It's essentially how content and fulfilled. Employee satisfaction is crucial to the success of an organization. Therefore, companies should focus on creating work environments that promote creativity, learning, self-expression, and autonomy to achieve self-actualization. This paper examines the importance of studying factors associated with employee satisfaction, highlighting their relationship with workplace well-being, employee development, employee retention, engagement, healthy workplaces, and trust. The surveys have six components and take about 10 to 15 minutes to complete. A link to a Google Form survey was supplied to respondents. These questionnaires undergo the pilot test and were distributed to the employee of the private institutions. The IBM SPSS Statistics Software "Version 27" will be used in this study to test the validity and reliability of the instrument’s items. The result of the study shows that all the independent variables influence the employee satisfaction. By understanding and prioritizing employee satisfaction, organizations can create a positive work environment that benefits everyone. Just like a well-cared-for plant, happy employees blossom and contribute to the overall success of the organization.